DOI: 10.18130/v3dj6t
|View full text |Cite
|
Sign up to set email alerts
|

Planar Laser Induced Iodine Fluorescence for the Investigation of the Aerodynamics of Reaction Control System Jets on Mars-Entry Aeroshells

Abstract: In order to improve landing accuracies on Mars in preparation for future manned mission, effort has been made in improving control of the vehicle through the use of reaction control system jets under rarefied conditions where normal control surfaces (ailerons, rudders, etc.) are ineffective. Despite their use on Apollo and Viking landers, as well as the space shuttle, firing the reaction control system (RCS) jets can have unanticipated effects on the aeroshell such as augmented heating and induced adverse forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…The data acquisition has been thoroughly discussed in Ref. 52, so a brief overview of the necessary steps to take prior to an experiment will be discussed, as well as the data output format. Further, the data analysis method and program written for this work, as well as the work in Ref.…”
Section: Chapter 3: Experimental Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The data acquisition has been thoroughly discussed in Ref. 52, so a brief overview of the necessary steps to take prior to an experiment will be discussed, as well as the data output format. Further, the data analysis method and program written for this work, as well as the work in Ref.…”
Section: Chapter 3: Experimental Design and Proceduresmentioning
confidence: 99%
“…It was concluded that a 2 cm diameter model would be sufficiently small to avoid unwanted interactions of the model bow shock with the freestream barrel shock. 52 However, 2 cm models with a PD jet were found to be too large and produce significant unwanted interaction of the two shock systems. An example of the interaction of the model bow shock and freestream barrel shock is shown for a 2 cm diameter model in Due to the increasing interaction with the freestream barrel shock at larger thrust, it was decided that quantitative experiments should be run at lower C T to reduce the interaction because it will not be modeled by CFD.…”
Section: Visualizationsmentioning
confidence: 99%